2010
DOI: 10.1002/hbm.20987
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia hypoactivity during grip force in drug naïve Parkinson's disease

Abstract: The basal ganglia (BG) are impaired in Parkinson's disease (PD), but it remains unclear which nuclei are impaired during the performance of motor tasks in early-stage PD. Therefore, this study was conducted to determine which nuclei function abnormally, and whether cortical structures are also affected by early-stage PD. The study also determined if cerebellar hyperactivity is found early in the course of PD. Blood oxygenation level dependent activation was compared between 14 early-stage drug-naïve PD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(114 citation statements)
references
References 34 publications
15
99
0
Order By: Relevance
“…Previous studies indicated these regions involved in motor control [45][46][47][48][49] and motor learning [50,51]. Therefore, here the role of the two regions may be involved with regulating the ongoing activity of motor cortex between EO and EC (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Previous studies indicated these regions involved in motor control [45][46][47][48][49] and motor learning [50,51]. Therefore, here the role of the two regions may be involved with regulating the ongoing activity of motor cortex between EO and EC (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…The focus is on motor task-based functional MRI using a reliable motor task, and diffusion MRI using novel analytic methods (10, 11). The goal is to develop unique candidate markers of progression in PD (in comparison to other movement disorders).…”
Section: Resultsmentioning
confidence: 99%
“…1a) because previous studies have shown reliable blood oxygen level-dependent (BOLD) activity changes in individuals with neurological disorders that include Parkinson’s disease, essential tremor, multiple system atrophy, and progressive supranuclear palsy (Burciu et al 2015; Neely et al 2015; Planetta et al 2015a; Spraker et al 2010). Further, our pilot data confirmed that SCA6 patients were able to execute pinch grip force with similar behavioral performance as age-matched healthy controls.…”
Section: Methodsmentioning
confidence: 99%
“…Using a grip force control fMRI paradigm (Neely et al 2015; Planetta et al 2015a; Spraker et al 2010), we explored task-based fMRI activity within sensory and motor cortex and cerebellum, and task-based functional connectivity between cortical motor regions (i.e., sensorimotor cortex and supplementary motor area: SMA) and cerebellum. In addition, free-water diffusion magnetic resonance imaging (dMRI) was assessed using a bi-tensor model to evaluate the tissue compartment and the free-water compartment within cerebellar regions (i.e., dentate, cerebellar lobules V and VI, cerebellar vermis, and peduncles).…”
Section: Introductionmentioning
confidence: 99%